KNOWLEDGE, ATTITUDE AND PRACTICES OF PAKISTANI GENERAL POPULATION ASSOCIATED WITH COVID-19; A CROSS SECTIONAL STUDY - Taimoor Ashraf Khan; Muhammad Mahad Qureshi; Anum Ehsan; Muhammad Abdullah Zahid; Muhammad Ashraf (Pakistan Armed Forces Medical Journal, 2020)
Objective: To know the knowledge, attitude and practices of Pakistani general population associated with COVID-19 outbreak and its correlation in different age groups, genders and educational status.